The integration of the developing countries into the world economy - Werner Glastetter (Intereconomics, 1988)
Despite decades of efforts, it has not yet been possible to integrate the developing countries satisfactorily into the world economy. Professor Glastetter examines the reasons for the failure of the integration strategies pursued hitherto and discusses the prospects of success with alternative approaches.
Keywords: 330; Development Strategy